Oridonin ameliorates renal fibrosis in diabetic nephropathy by inhibiting the Wnt/β-catenin signaling pathway - Jushuang Li; Lan Shu; Qianqian Jiang; Baohong Feng; Zhimin Bi; Geli Zhu; Yanxia Zhang; Xiangyou Li; Jun Wu (Renal Failure)
Diabetic nephropathy (DN) is one of the most serious and frequent complications among diabetes patients and presently constitutes vast the cases of end-stage renal disease worldwide. Tubulointerstitial fibrosis is a crucial factor related to the occurrence and progression of DN. Oridonin (Ori) is a diterpenoid derived from rubescens that has diverse pharmacological properties. Our previous study showed that Ori can protect against DN by decreasing the inflammatory response. However, whether Ori can alleviate renal fibrosis in DN remains unknown. Here, we investigated the mechanism through which Ori affects the Wnt/β-catenin signaling pathway in diabetic rats and human proximal tubular epithelial cells (HK-2) exposed to high glucose (HG) levels. Our results revealed that Ori treatment markedly decreased urinary protein excretion levels, improved renal function and alleviated renal fibrosis in diabetic rats. In vitro, HG treatment increased the migration of HK-2 cells while reducing their viability and proliferation rate, and treatment with Ori reversed these changes. Additionally, the knockdown of β-catenin arrested cell migration and reduced the expression levels of Wnt/β-catenin signaling-related molecules (Wnt4, p-GSK3β and β-catenin) and fibrosis-related molecules (α-smooth muscle actin, collagen I and fibronectin), and Ori treatment exerted an effect similar to that observed after the knockdown of β-catenin. Furthermore, the combination of Ori treatment and β-catenin downregulation exerted more pronounced biological effects than treatment alone. These findings may provide the first line of evidence showing that Ori alleviates fibrosis in DN by inhibiting the Wnt/β-catenin signaling pathway and thereby reveal a novel therapeutic avenue for treating tubulointerstitial fibrosis.